KELIMPAHAN FUNGI MIKORIZA ARBUSKULA (FMA) PADA TEGAKAN EKALIPTUS (Eucalyptus pellita) BERDASARKAN TINGKAT KEDALAMAN DI LAHAN GAMBUT - Hermawan, Helmi; Muin, Abdurrani; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2015)
The objective of the research is to find abundance of Arbuscular Mycorrhizal Fungi (AMF) at each depth of plant E.pellita that located on peatland in HTI PT. Kalimantan Subur Permai. The results of the research show that up to 100 cm soil depth was found AMF spores. Spores abundance increased with increasing depth of peat. At a depth of 0-20 cm was found as much as 317 spores/100 g of peat, depth of 20-40 cm 360 spores /100 g of peat, depth of 40 - 60 as much as 428 spores/100 g of peat, depth of 60 - 80 as much as 315 spores/100 g peat and 80 - 100 cm 234 spores/100 g of peat. The highest number is found at a depth of 40-60 cm and a depth of 60 cm more than the number of spores found on the wane. Based on the distance from the sampling of plant E. pellita, it turns out there is a difference between a distance of 30 cm by 60 cm. Spore abundance is higher at a distance of 60 cm sampling compared with 30 cm. The results also showed that in HTI PT. Kalimantan Subur Permai built on peat more a lot of genus Glomus. Based on the observations of the characteristics of the type of spores were found in HTI area there are 8 species of mycorrhizal fungi that needs to be further identified. Keyword : Abundance, arbuscular mycorrhizal fungi,depth of peatland, E. pellita